Scenting extinction. (Economist, 1991)
Contends that, by clinging to its mainframe business and the ways of selling computers that went with it, IBM has jeopardized its future. How Chairman John Akers is trying to move away from mainframes; View of analysts that swift changes are needed; Passage of the age of mainframe computing; Mistrust; Reliance on cost-cutting.